Property inviolability in legal and philosophical vision - A.Ja. Ryzhenkov (Ученые записки Казанского университета: Серия Гуманитарные науки)
The paper is devoted to understanding the philosophical importance of the principle of inviolability of property. The conclusion has been made that the idea of the inviolability of property is characterized by an inherent latent conflict between the individualistic and collectivist attitudes that, in turn, can be traced to the relation between philosophical categories of part and whole. The inviolability of property means that the items that belong individually to a certain person or group of persons may not, without the consent of the owner, become the property of someone else. In other words, it is assumed that the owner together with the property belonging to them is isolated from other members of society. The opposite approach is based on the fact that society as a whole is primary in relation to its constituent elements. Moreover, it has its own needs, which have priority over the needs of individuals and social groups. In this case, property is only a social convention, which is more permissive than mandatory, i.e., it can be revised if necessary.